SIBERIA IN V. SHAMALOV'S PROSE: ON THE PROBLEM OF THE SPATIAL ORGANIZATION OF THE TEXT - Oshchepkova, Anna (Revista Inclusiones, 2020)
The article considers the features of the spatial organization of "Kolyma Tales" by V. Shalamov in the context of Siberian discourse. The "points of view" in the stories "Bread" (1956) and "The Letter" (1966) are analyzed in terms of their spatial and temporal characteristics.